(untitled) (Western European Journal of Medicine and Medical Science, 2024)
Nowadays, people are facing numerous challenges in their professional, social, and personal lives due to rapidly changing circumstances and high expectations. Persistent stress, pressure, and lack of time have become primary factors contributing to the development of neurotic disorders. During the COVID-19 pandemic, many individuals experienced insecurity, concerns about the health of their loved ones, or economic uncertainties. These factors led to an increase in conditions such as neurosis and anxiety. Many people struggle to balance their work and personal lives, resulting in mental fatigue and neurosis. This condition is especially prevalent among individuals in high-responsibility jobs. Neurosis has become increasingly relevant in modern times due to various factors, and its early diagnosis, treatment, and prevention are crucial for maintaining mental health.